TRANSIENT VIBRATION ANALYSIS OF A TURNING MACHINE, S SPINDLE - A. Mahdavinejad, R. (Journal of Engineering & Processing Management, 2009)
Spindle is one of the most important member in turning machines, so that its precision determines the dimensional tolerances of machined parts. In this paper, the spindle’s response to standard input parameters has been analyzed via Finite Element Method (FEM).From this point of view, the spindle of LZ330VS turning type machine is modeled with Solid Works software. Then, the model is meshed via Msc-Patran software and analyzed by ANSYS. Four values which are the same for all inputs are applied to each one to study the affection of input parameters on the model, simultaneously. The results show that increasing in applied loads increases the oscillating dominations. The value of applied forces has also more affection than the applying time and input type on the oscillating dominations.